Komparasi wali mujbir dalam mazhab Syafi’i dan mazhab Hanafi - Aditya, Muzemmil; Yuliardy Nugroho, Irzak (Prodi Perbandingan Madzab Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2023)
This article discusses a comparison of the thoughts of the Hanafi school of thought and the Syafi'i school of thought. The author uses data collection methods with documentation techniques. After obtaining the required data, the data is analyzed using the comparative analysis method. The Syafi`i school of thought says that as long as a girl still has the status of al-bikr (girl) then the rights of a guardian still exist. The limit for al-bikr (girl) according to the Syafi`i school is as long as the woman has never had sexual intercourse (jima`), even if she has had sexual intercourse. If adultery is committed, the person is no longer considered al-bikr (girl), this statement from the Shafi'i school includes a girl who is divorced by her husband but has never had sexual intercourse with him (qobla dukhul), because essentially the woman still has the status of al-bikr (girl). Meanwhile, according to the Hanafi school of thought, those who have the right to become mujbir guardians are all guardians from the father's line, while mujbir guardians can only be applied to girls who have not reached puberty. The Hanafi school also imposes requirements for mujbir guardians, namely that they must be able to provide a suitable husband for their daughter. Meanwhile, all trustees for crazy people are mujbir trustees. Mujbir is just a father and grandfather. From this background, the author is interested in discussing the opinions of Imam Hanafi and Imam Syafi'i on the issue of wali mujbir. This article contains the opinions and methods of legal istinbat used by Imam Hanafi and Imam Syafi'i regarding wali mujbir. The method of istinbat wali mujbir used by Imam Syafi'i is the Koran, Sunnah, and Qiyas, while the method of legal istinbat used by Imam Hanafi in the matter of wali mujbir is the Koran, Sunnah, and 'Urf. The illat used by Imam Syafi'i is bikr (virginity), while the illat used by Imam Hanafi in the concept of ijbar guardianship is ghairu aqilah. Because women in this situation are unable to do anything for themselves